ANALISIS PREFERENSI PLATFROM E-COMMERCE DAN PERILAKU BELANJA KONSUMEN DIGITAL LINTAS GENERASI DI PASAR INDONESIA - Zerah Elisa Derek; Yoan Purnamsari Makapuase Bahalau; Marthin Thomas Mumbunan (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the impact of generational characteristics on e-commerce platform preferences and purchasing decisions in Indonesia. By analyzing Gen Z, Millennials, and Baby Boomers, the research highlights a significant shift in digital behavior. Gen Z predominantly favors visual-based platforms like TikTok Shop, driven by social trends and "shoppertainment," whereas Baby Boomers rely on conventional marketplaces like Tokopedia for structured navigation. Despite these differences, Shopee maintains cross-generational dominance through functional excellence, specifically via integrated payment methods like COD, aggressive discounting, and free shipping incentives. The findings reveal that while Gen Z’s final purchase decisions are motivated by social validation, older generations prioritize security and trust. This study concludes that a platform’s success depends on its ability to balance innovative visual engagement with robust functional reliability. These insights provide a strategic framework for e-commerce entities to tailor their services to the diverse psychological and functional needs of Indonesia's multi-generational digital market. Keyword : E-commerce, Generational Cohorts, Consumer Behavior, Platform Preference, Digital Transactions, Loyalty Factors, Shopee, Indonesia.